UNCITRAL--the United Nations Commission on International Trade Law. - United Nations Commission on International Trade Law. (New York : United Nations, 1986)
The book is to acquaint the readers (scholars, practitioners and researchers) as well as to those with more general interests with the United Nations Commission on International Law (UNCITRAL)and its work towards the harmonization and unification of the law of international trade .
gp. 23/01/2019
Loan
Keywords: Foreign trade regulation; Commercial law; Law